Ethiopia - Capturing the Demographic Bonus in Ethiopia : Gender, Development, and Demographic Actions - World Bank (Washington, DC, 2012)
This is a sector report on demographics in Ethiopia. The first part of this study puts the population issue in Ethiopia in perspective. Chapter 1 updates Ethiopia's demographic profile, looking in particular at the size of its population, its age structure, the speed at which it grows and its distribution across space. Chapter 2 explores the relationships between population growth, economic growth, and poverty within the Ethiopian context. Chapter 3 examines how Ethiopia has attempted to deal with its demographic challenges. In particular, it reviews the policies that have been developed, assesses their implementation, and analyzes how they relate to the new development paradigms, in particular, the poverty reduction strategies and the achievement of the MDGs. Chapter 4 concludes the review of population, poverty and policy-related issues in Ethiopia today. The second part of the study gauges the effect of the current development strategy on the prospects for population growth, economic growth, and poverty reduction in Ethiopia.